Considering preferences, speed and the animation of multiple symbols in developing P300 brain-computer interface for children. - Pitt, Kevin M.; Spoor, Austin; Zosky, Joshua (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: Prior research has begun establishing the efficacy of animation in brain-computer interfaces access to augmentative and alternative communication (BCI-AAC). However, the use of animation in P300-BCI-AAC for children is in the early stages and largely limited to single item highlighting of extended durations. In pursuit of practical application, the present study aims to evaluate children's event-related potential (ERP) characteristics and user experience during a task involving an animated P300-BCI-AAC system. Materials and methods: The system utilizes multi-item zoom animations to access a 28-pictorial symbols. Participants completed a fast (100 ms) and slow (200 ms) zoom animation highlighting conditions wherein four pictorial symbols were highlighted concurrently. Results: The proposed display appears feasible, eliciting all targeted ERPs. However, ERP amplitudes may be reduced in comparison to single-item animation highlighting, possibly due to distraction. Ratings of mental effort were significantly higher for the 100 ms condition, though differences in the frontal P200/P300 ERP did not achieve significance. Most participants identified a preference for the 100 ms condition, though age may impact preference. Conclusions: Overall, findings support the preliminary feasibility of a proposed 28-item interface that utilises group zoom animation highlighting of pictorial symbols. Further research is needed evaluating ERP characteristics and outcomes from online (real-time) use of animation-based P300-BCI-AAC for children with severe speech and physical impairments across multiple training sessions. IMPLICATIONS FOR REHABILITATION: The proposed display employing multi-item zoom animations seems feasible. However, preliminary evidence suggests that event-related potential amplitudes may be reduced compared to single-item animation highlighting. Number scale ratings of mental effort were significantly higher for the 100 ms condition. Most participants identified a preference for the 100 ms condition, although age may impact preference.